Synthesis and Biological Activities of Novel Quinazoline–Sulfonamide Derivatives Promising for the Treatment of Alzheimer's Disease - Bükülmez, Gönül; Mert, Samet; Turkan, Fikret; Nuri Atalar, Mehmet Nuri; Bursal, Ercan; Kasimogullari, Rahmi (John Wiley and Sons Inc, 2025)
Novel quinazoline–sulfonamide derivatives (4a-n) were synthesized and evaluated for their enzyme inhibitory activities against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) which are associated with Alzheimer's diseases (AD). The target quinazoline–sulfonamides (4a-n) were obtained via one-pot multicomponent reaction of 5-amino-1,3,4-thiadiazole-2-sulfonamide (1) with substituted benzaldehydes (2a-i) and cyclohexane-1,3-diones (3a,b) under microwave irradiation. The reactions were performed using trifluoroacetic acid (TFA) as catalyst and methanol–water mixture as green solvent. All reactions were carried out in a short period of time and the products were obtained in moderate-to-high yields and their structures were confirmed using 1H-NMR, 13C-NMR, Fourier-transform infrared (FT-IR), and mass spectroscopic techniques. AChE and BChE enzyme inhibitions were obtained from the lowest Ki and IC50 values. The lowest Ki values of compounds 4j, 4d, 4e, and 4m were determined to be 4.84 ± 1.96 µM, 6.32 ± 1.75 µM, 7.21 ± 3.27 µM, and 7.48 ± 0.42 µM against AChE, while the lowest Ki values of compounds 4d, 4f, and 4j were determined to be 4.74 ± 1.98 µM, 5.87 ± 2.11 µM, and 5.67 ± 1.96 µM against BChE, respectively. Finally, in silico molecular docking interactions were carried out by using AutoDock Vina software. The low binding energy values of the compounds (4a-4n) against AChE and BChE enzymes indicated their high inhibitory effectiveness. © 2025 Elsevier B.V., All rights reserved.
Keywords: 1,3,4-thidiazole; Enzyme Inhibition; Molecular Docking; Quinazoline, Sulfonamide